Pengaruh Variasi Holding Time Terhadap Struktur dan Sifat Resistifitas dan Konduktifitas ZnO Dengan Doping Ni - Gultom, Golfrid (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2024)
This study aims to determine the effect of holding time variations on the structure, electrical and magnetic properties of ZnO doped with Ni. The fabrication of the samples used the solid state reaction method with a high speed shaker mill and continued with sintering at temperature of 900oC with variable holding time of 2, 4 and 8 hours. Samples doped with Ni have a hexagonal wurtzite polycrystalline structure. The holding time treatment causes a shift in the diffraction peak in the Ni-doped ZnO. This indicates a change in crystal parameters such as lattice parameters and crystal size. The crystal size of Zn0.97Ni0.03O increased with increasing holding time. The longer the holding time, the longer the diffusion that occurs from the heat effect, so that the small grains have sufficient time to combine (agglomerate) into large grains. The resistivity of Zn0.97Ni0.03O samples with holding time of 2, 4 and 8 hours was obtained increasing which caused a decrease in the conductivity value of Zn0.97Ni0.03O.